2020
DOI: 10.1002/jbmr.4563
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Romosozumab Among Postmenopausal Women With Osteoporosis and Mild-to-Moderate Chronic Kidney Disease

Abstract: Patients with osteoporosis and chronic kidney disease (CKD) are at increased risk of fracture and associated negative outcomes, including increased mortality. The present post hoc analysis of two randomized, multicenter, phase 3 clinical trials-Fracture Study in Postmenopausal Women with Osteoporosis (FRAME) and Active-Controlled Fracture Study in Postmenopausal Women with Osteoporosis at High Risk (ARCH)-investigated the efficacy and safety of romosozumab in postmenopausal women with osteoporosis and mild-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…Although renal dysfunction is a risk factor associated with the development of hypocalcemia upon denosumab administration ( Tsvetov et al, 2020 ), our results showed that the degree of reduction in calcium concentration upon romosozumab administration was not affected by renal function. In support of our findings, in a post-hoc study of clinical trials, the degree of decrease in serum calcium did not differ between patients with moderate renal dysfunction and those without renal dysfunction ( Miller et al, 2022 ). However, it should be noted that in our study population, the creatinine concentrations were within the normal range in most patients; thus, we were not able to evaluate patients with impaired renal function.…”
Section: Discussionsupporting
confidence: 87%
“…Although renal dysfunction is a risk factor associated with the development of hypocalcemia upon denosumab administration ( Tsvetov et al, 2020 ), our results showed that the degree of reduction in calcium concentration upon romosozumab administration was not affected by renal function. In support of our findings, in a post-hoc study of clinical trials, the degree of decrease in serum calcium did not differ between patients with moderate renal dysfunction and those without renal dysfunction ( Miller et al, 2022 ). However, it should be noted that in our study population, the creatinine concentrations were within the normal range in most patients; thus, we were not able to evaluate patients with impaired renal function.…”
Section: Discussionsupporting
confidence: 87%
“…In the post hoc analyses of 2 pivotal phase 3 clinical trials assessing romosozumab, namely, ARCH and FRAME, similar efficacy and safety of romosozumab was observed in women with postmenopausal osteoporosis with normal renal function and in those with mild to moderate CKD. 23 Additionally, in a recent study, improvement in bone density was reported after 6 months of romosozumab treatment in patients with osteoporosis requiring hemodialysis. 24 Thus, increase in BMD after romosozumab treatment does not seem to be dependent on the stage of RI in the patient.…”
Section: Discussionmentioning
confidence: 96%
“…In the post hoc analysis of phase 3 trials, FRAME and ARCH, of 9770 women with postmenopausal osteoporosis and mild to moderate CKD, only 2 women with mild CKD and treated with romosozumab reported AEs of mild to moderate hypocalcemia. 23…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Moe et al demonstrated in a CKD rat study that in the presence of high levels of PTH, serum Ca levels were lower than in the low PTH group independently of the class of anti-osteoporotic drugs, and the efficacy of romosozumab was reduced due to the activation of Wnt signaling by PTH that may bypass the LRP signaling ( Moe et al, 2015 ). Two recent post hoc analyses investigated the efficacy and safety of romosozumab among postmenopausal women with osteoporosis and mild-to-moderate CKD (stages 1–3) ( Miller et al, 2022 ; Miyauchi et al, 2022 ). Both studies demonstrated that BMD at the lumbar spine, total hip, and femoral neck, significantly increased as a result of treatment with romosozumab for 1 year.…”
Section: Discussionmentioning
confidence: 99%